Impact of Demographic Factors on Oral Health Knowledge and Attitude of patients with Type II Diabetesmellitus Visiting A THQ Hospital in Punjab, Pakistan - Farhan Riaz, Afifa Ehsan, Ali Raza, Umer Abdullah, Muhammad Mutahir Mehdi, Ejaz Hussain Sahu, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim:Patients suffering from Diabetes Mellitus havea largerpossibilityofdeveloping oral diseases furthermore; those who have uncontrolled and long-duration of Diabetes Mellitusare also at a greater risk for acquiringperiodontaldisorders. The present study intended to investigate the association of oral fitness knowledge and attitude with different demographic factorsin patients with Type II Diabetes Mellitus visiting a secondary care provincial hospitalin Sargodha, Pakistan. Methods: The present study was a cross-sectional study piloted at a secondary care provincial hospital in District Sargodha which comprised 180 patients suffering from Type II Diabetes Mellitus.Information was collected using a systematized questionnaire which was handed out to study participants visiting the outpatient department of the hospital. Results:Oral health knowledge of the study participants were cross-tabulated with socio-economic and demographic factors and a significant association was seen with gender(P≤0.001), educational status(P≤0.0001), monthly income(P≤0.002), and marital status(P≤0.001). In the present study, 26% of males and 18% of females had adequate knowledge regarding oral health. Advanced levels of learningand income also transpiredto have a strong association with oral health awarenessand attitude(P≤0.01). Conclusions: Results of the present study suggest that oral well-being knowledge and attitude among patients with Type II Diabetes Mellitus were strongly associated in conjunction withgender, higher levels of education, and income. Based on these outcomes, communal-oriented oral well-being campaigns are indispensable to navigating the standard of living of patients with Type II Diabetes Mellitus. Keywords: Dental, Diabetes Mellitus, Knowledge, Oral Health, Oral complications, Type II Diabetes Mellitus.